Effect of muramidase fouling on nanofiltration of estrone - Teh, Suk Yen. (2010)
Protein (Muramidase) fouling and its effects on rejection of Estrone (E1) by two nanofiltration membranes (NF90 and NF270) were investigated in this study. Fouling conditions were achieved with Muramidase (lysozyme) added in a 50L Milli Q water with 10mM ionic strength. The effects of membrane fouling on the separation process were investigated by comparing the rejection values of clean and fouled membranes and relate them to their membrane pore size as well as physicochemical characteristics of Estrone. Results reported in this study suggest that rejection of trace Estrone by clean NF membranes was governed by steric hindrance and hydrophobic interactions. The estrone’s hydrophobicity was suggested to be influenced only the rejection in the initial stage of filtration based on the similar rejection of Estrone by NF270 and NF90 found at the initial stage of filtration. Nevertheless, steric exclusion (or size exclusion) appears to be the most prevalent mechanism controlling not only retention of both trace Estrone and salt, but also the membrane fouling process as well as the effects of fouling on the retention. Both fouled and clean NF90 performed near complete (<80%) and higher rejection of estrone than membrane NF270 in clean and fouled condition. The improved Estrone rejection on fouled membrane can be attributed to the formation of cake layer which may trigger stronger electrostatic repulsion between Estrone and cake layer attached on the membrane surface. Adsorption of Estrone onto the cake layer is possible due to the highly hydrophobicity of Estrone and the special characteristics of protein (Muramidase) with the tendency to cluster with hydrophobic compounds. The contact angles of both membranes were altered after fouling process. Pore blocking and cake layer formation are believed to cause fouling behavior such as permeate flux decline. The permeate flux decline was found to be more severe in NF90 due to the dense cake layer formation. There is a good correlation found between the trans-membrane pressure applied and the severity of flux decay. With a specific membrane type, the permeate flux decline tends to achieve a certain level regardless of their trans-membrane pressure applied. No clear influence brought by fouling was found in feed and permeate solution in terms of the conductivity change.